Trojan Horse of The Cold War: Nowa Huta as the Instrument of Soviet Influence on the Polish People’s Republic (City: History, Culture, Society, 2023)
The article examines the exertion of power by the Soviet Union during the Cold War on the territory of the Polish People's Republic through economic and urban planning mechanisms, exemplified by the construction of Nowa Huta. It specifically delves into the Soviet intervention in the structural reorganisation of both the city and the plant, as well as the consultations between Polish and Soviet experts. The article highlights that the Soviet influence was evident, ranging from adopting the Soviet model of forced industrialization and construction management to the daily control of technological processes in production. The propagandist image of Nowa Huta constantly emphasises its importance as one of the prime symbols of Polish-Soviet friendship and a symbol of peace, aligning with the Cold War rhetoric. Finally, contemporary historiography and collective memory conceptualise the perception of Nowa Huta as a legacy of the Cold War, in particular through its museumification and categorization within the framework of an uncomfortable heritage.
Keywords: Nowa Huta; cold war; propaganda; socialist city; industrial heritage; inconvenient heritage